Unveiling the potential anticancer activity of Spirulina maxima extract-nanoemulsion through in vitro and in vivo studies - Mohammed Yasser Hussein; Merna Nasr; Veronia Emad; Julie Maged; Portia George; Amina Emad; Abeer Mahmoud Badr; Mehrez E. El-Naggar; Sayeda M. Abdo; Jihan Hussein (Scientific Reports)
Abstract Being the second leading cause of death globally, cancer has been a long-standing and rapidly evolving focus of biomedical research and practice in the world. Recently, there has been growing interest in cyanobacteria. This focus is particularly evident in developing innovative anticancer treatments to reduce reliance on traditional chemotherapy. This study investigates the anticancer potential of the Spirulina maxima extract nanoemulsion (SMNE) technique to improve the delivery, stability, and solubility of the S. maxima extract (SME). SMNE, prepared in three concentrations (SMNEC1, SMNEC2, SMNEC3), was characterized and confirmed to successfully load SME into silica-coated nanoparticles. Cytotoxicity tests on HepG2 and MCF-7 cell lines revealed a significant reduction in cell viability after 48-hour SMNE treatment, with IC50 values of 1488 µg/mL and 1721.936 µg/mL, respectively. SMNE also demonstrated efficacy in inhibiting tumor growth in mice with Ehrlich ascites carcinoma, normalizing alanine aminotransferase (ALT) and aspartate aminotransferase (AST) levels, and reducing oxidative stress markers such as catalase (CAT) and malondialdehyde (MDA). Histopathological examination showed that SMNEC3-treated groups had almost normal liver architecture. Additionally, SMNE downregulated oncogenic miR-221-3p and miR-222-3p, activating cancer suppression genes p27 and PTEN. The study concludes that SMNE, with its anti-inflammatory and antioxidant properties and ability to modulate key miRNAs, enhances SME delivery and shows promise as an effective cancer treatment.